AKSELERASI PEMAHAMAN DAN KESADARAN MASYARAKAT MENGENAI PENTINGNYA LITERASI DATA DAN DIGITALISASI DI ERA 5.0 - Achmadi, Caesar Rosyad; Puspita, Noni; Makarim, Muhammad Harfiansyah; Nugraha, R. Andro Zylio; Saputri, Agatha (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Globalization drives the rapid development of technology. Society at this time has begun to enter the industrial era 5.0. The industrial era 5.0 is closely related to the use of data in various aspects and fields. Data is also fundamental in various aspects such as education, demographics, economics, health, and other aspects. Since almost all aspects of people's life activities today are data-based, data literacy is very important. However, the facts in the community have not been able to realize the importance of data literacy, so it has not been well socialized. The purpose of this community service activity is to increase the understanding of data literacy in SMA N 1 Wonosari Yogyakarta students with teaching materials named â€œUnleashing The Power of Dataâ€. The methods used in this activity are presentation and discussion. From the evaluation results using pre-test and post-test, it was found that the average student still had an understanding of data literacy below 50%. After this activity, the post-test showed that the understanding of data literacy increased above 85%. This activity was attended by 35 students of SMA N 1 Wonosari Yogyakarta. It can be concluded that this activity increases the understanding of data literacy in SMA N 1 Wonosari Yogyakarta students. Keywords: data literacy, community service, understanding data in era 5.0